2015
DOI: 10.1111/zoj.12298
|View full text |Cite
|
Sign up to set email alerts
|

An underground burst of diversity - a new look at the phylogeny and taxonomy of the genusTalpaLinnaeus, 1758 (Mammalia: Talpidae) as revealed by nuclear and mitochondrial genes

Abstract: Using both nuclear and mitochondrial sequences, we demonstrate high genetic differentiation in the genus Talpa and confirm the existence of cryptic species in the Caucasus and Anatolia, namely, T. talyschensis Vereschagin, 1945, T. ognevi Stroganov, 1948, and Talpa ex gr. levantis. Our data support four clades in the genus Talpa that showed strong geographical associations. The 'europaea' group includes six species from the western portion of the genus' range (T. europaea, T. occidentalis, T. romana, T. caeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 59 publications
(64 reference statements)
2
29
0
Order By: Relevance
“…According to the Genetic Species Concept, the species threshold is determined based on the level of differentiation between known genetically isolated lineages (Baker & Bradley, ; Bradley & Baker, ). The essential mitochondrial genetic distance between M. wogura and M. robusta (~6%) corresponds to those between pairs of the sister species in other groups of the strictly fossorial moles such as Talpa or Euroscaptor (Bannikova et al., ; Nicolas, Martínez‐Vargas, & Hugot, ; Tsuchiya et al., ; Zemlemerova, Bannikova, Lebedev, Rozhnov, & Abramov, ). The phylogeographic break might have occurred when the Korea Strait could block gene exchange between these two lineages.…”
Section: Discussionmentioning
confidence: 98%
“…According to the Genetic Species Concept, the species threshold is determined based on the level of differentiation between known genetically isolated lineages (Baker & Bradley, ; Bradley & Baker, ). The essential mitochondrial genetic distance between M. wogura and M. robusta (~6%) corresponds to those between pairs of the sister species in other groups of the strictly fossorial moles such as Talpa or Euroscaptor (Bannikova et al., ; Nicolas, Martínez‐Vargas, & Hugot, ; Tsuchiya et al., ; Zemlemerova, Bannikova, Lebedev, Rozhnov, & Abramov, ). The phylogeographic break might have occurred when the Korea Strait could block gene exchange between these two lineages.…”
Section: Discussionmentioning
confidence: 98%
“…The taxonomic status of these lineages deserves additional studies considering the observed chromosomal difference relative to the general conservation of karyotype in the genus (Gornung et al 2008). The time of divergence between the two T. caeca lineages (about 1 MYA) is close to the maximum limit of intraspecific divergence in the genus Talpa (Bannikova et al 2015).…”
Section: Candidate Endemic Speciesmentioning
confidence: 93%
“…Recent genetic molecular studies found that T. caeca has segregated into an Italian and a Balkan lineage (Bannikova et al 2015). The taxonomic status of these lineages deserves additional studies considering the observed chromosomal difference relative to the general conservation of karyotype in the genus (Gornung et al 2008).…”
Section: Candidate Endemic Speciesmentioning
confidence: 99%
“…Although studies have considered the potential role of Anatolia as a glacial refugium for some species (Bilgin, ; Hewitt, ), phylogeographical analyses related to the potential refugia in the Anatolian region are scarce. Molecular studies on the mammal species distributed in Turkey, such as rodents, carnivores and some insectivores, have suggested that these populations harbour unique genetic lineages, either in terms of haplotypes or evolutionarily significant units (Aksöyek, İbiş, Özcan, Moradi, & Tez, ; Bannikova et al., ; Dubey, Diker, Kurtonur, & Vogel, ; Dubey et al., ; Gündüz, Rambau, Tez, & Searle, ; Gündüz et al., , ; İbiş, Aksöyek, Özcan, & Tez, ; İbiş, Tez, & Özcan, ; İbiş et al., ; Neumann et al., ).…”
Section: Introductionmentioning
confidence: 99%